Integration and Regulation of Financial Markets (A Case of an Insurance Market) - Čarný, Ján; Kadeřábková, Božena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2018)
Economic theory predicts reduced demand for durable goods from companies with greater risk of future bankruptcy. A new regulation on the Czech insurance market requires companies to publish quarterly detailed data about their financial health (and a host of other data), in the hope that insurance buyers will adjust their purchases of insurance contracts (a durable good) accordingly. This thesis tests econometrically panel data on quarterly company sales of insurance (Life, Non-Life, Automotive) for sensitivity to financial health data published in compliance. Controlling for literature-standard demand factors, it finds no effect on any of the three markets under any of the three tested specifications of how customers interpret the data. The thesis also analyses the available alternatives which protect consumers from insurer bankruptcy even without the regulation, to argue that removing it could be a net social benefit. This proposition is supported by international research, which also suggests that certain provisions of the regulation (e.g. attention to gender-related pricing) could work to increase rather than decrease the risk of an insurer’s financial problems. The analysis draws up recommendations for economic policy.
Vedoucí práce: Božena Kadeřábková
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: hospodářská politika [obor disert. práce]; disertace; dissertations